Pemanfaatan Limbah Pabrik Kelapa Sawit Sebagai Kompos Dengan Variasi Penambahan Dosis Abu Boiler Serta Penggunaan Bioaktivator EM-4 - Putra, Anggara; Yenie, Elvi; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm Oil Mill Effluent treatment produces sludge as byproduct. Without being processed, the sludge will cause damage to environment and industry. The aim of this research is to convert the sludge, combined with boiler ash and palm oil fiber and litter of dry leaves into compost by using EM-4 as the activator. The instrument needed is a simple composter with height 40 cm and diameter 30 cm. The variations of the boiler ash dosage are 1 kg, 1,5 kg and 2 kg and the variations of composting time is 21 days in order to analyze the compost quality produced. The research showed that compost with 1 kg boiler ash dosage processed for 21 days resulted to a C/N ratio that meets SNI’s requirement 19-7030-2004 C/N ratio=11,72. The conversion of palm’s oil sludge into compost can be used as an alternative in utilization waste into valuable product.Keywords: boiler ash, EM-4 activator, compost, fiber, palm’s sludge